Mekanisme Tata Kelola Internal dan Pengungkapan Antikorupsi Perusahaan di Indonesia - Destia Dwi Putri; Yuni Putri Yustisi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to empirically examine the relationship between internal governance mechanisms and corporate anti-corruption disclosure in Indonesia. Internal governance mechanisms tested are independence of board, audit committee, ownership concentration, and family ownership. This research is a cross sectional study with a quantitative approach, the data used is secondary data. The sample of the study is 100 non-financial companies in Indonesia which are listed on Indonesia Stock Exchange with the largest market capitalization in 2019. This study finds that the internal governance mechanism on the part of audit committee has a positive influence on corporate anti-corruption disclosure. This shows that the role of audit committee has a major influence increasing transparency in preventing corrupt practices in the company environment.